The Effect of Video-Based Education on the Knowledge of Bone Fracture First Aid Blinds in Health Cadres in Kayubulan Village, Batudaa Pantai District - Sugiatman Pramana Putra Dunggio; Haslinda Damayansyah; Pipin Yunus (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Introduction: The use of splints for dressing is a crucial step in first aid for injuries, especially fractures. Efficient education is needed to improve health workers' understanding of this treatment method so they can provide appropriate first aid and reduce the risk of complications. Objective: This study aims to analyze the impact of video-based education on improving health workers' knowledge regarding the use of splints as a first aid method for bone fractures in Kayubulan Village, Batudaa Pantai District. Method: A quantitative study with a pretest-posttest quasi-experimental design was conducted on 17 health workers who met the inclusion requirements. The knowledge of the health workers was measured before and after receiving structured and easy-to-understand video-based education. Results: Before and after (Pretest-Posttest) the video-based education, the participants obtained an average mean of -6.353 and a standard deviation of 3.020. Using the Paired T-test, the value of p = 0.000 < ? = 0.05 was obtained. Therefore, there was an increase in the understanding of health cadres regarding the knowledge of splinting for first aid for bone fractures. Conclusion: Video-based education can improve the understanding of health cadres regarding the knowledge of splinting for first aid for bone fractures.